Advertisement Remove all ads

Show that ∫ a 0 √ X 3 a 3 − X 3 D X = a √ X γ ( 5 6 ) γ ( 1 3 ) - Applied Mathematics 2

Sum

Show that `int_0^asqrt(x^3/(a^3-x^3))dx=a(sqrtxgamma(5/6))/(gamma(1/3))`

Advertisement Remove all ads

Solution

Let `"I"=int_0^asqrt(x^3/(a^3-x^3))dx`

Put `x^3=a^3t  =>x=at^(1/3)`
Diff. w.r.t. x ,

`dx=a/3t^((-2)/3) dt`

Limits becomes →[𝟎,𝟏]

`"I"=int_0^1(t)^(3/2)(1-t)^(3/2)t^((-2)/3)a/3dt`

`=a/3int_0^1t^(5/6)(1-t)^(3/2)dt`

`=a/3beta(5/6,3/2)`

`"I"=a(sqrtxgamma(5/6))/(gamma(1/3)` …………{ from the definition of beta function}

Concept: Differentiation Under Integral Sign with Constant Limits of Integration
  Is there an error in this question or solution?
Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×